Bus Rapid Transit Accessibility Guidelines - Rickert, Tom (World Bank, Washington, DC, 2014)
In recent years helpful guides have appeared in both English and Spanish to assist planners and officials to construct accessible buildings and pedestrian infrastructure which are usable by seniors, persons with disabilities, and all others who especially benefit from universal design. Less has been written about access to public transport systems. Very little guidance is available concerning specific issues which confront those planning Bus Rapid Transit (BRT) systems, mass transit systems which incorporate a spectrum of design and operational features on integrated trunk and feeder routes and which were initiated in Latin America and are now spreading throughout the region and beyond. The guidelines focus on the BRT environment and assume that interested parties can take advantage of existing guidelines to clarify general issues of access to public space, buildings, and pedestrian infrastructure. The guidelines generally follow the travel path of a passenger using a full-featured Bus Rapid Transit system. The accessible travel chain begins with sidewalks and pedestrian crossings and continues into a typical mid-island station served by buses with left-side doors (in countries where traffic drives on the right side). Buses pull up to an enclosed station with a ramped platform the height of the bus floor. The guidelines then focus on station features, crossing the gap into the bus, and bus features. Due to the integrated nature of BRT, the guidelines focus equally on both trunk line and feeder line issues while acknowledging that a long-term planning process may be needed to identify funding for improved feeder line infrastructure and vehicles.